Computer-assisted discovery of safe and effective DprE1/ aaRSs Inhibitors against TB utilizing Drug Repurposing approach. Issue 4 (April 2023) - Imran, Mohd.; Abida,; Alotaibi, Nawaf M.; Thabet, Hamdy Khamees; Alruwaili, Jamal Alhameedi; Asdaq, Syed Mohammed Basheeruddin; Eltaib, Lina; Kamal, Mehnaz; Alshammari, Amal Bader Hommod; Alshammari, Abdulmajeed Mohammed Abdullah; Alshehri, Ahmed
Abstract: Background: The emergence of various drug-resistant strains of Mycobacterium tuberculosis compelled medicinal chemists to expedite the discovery of novel, safer alternatives to present regimens. Decaprenylphosphoryl-β-d -ribose 2′-epimerase (DprE1), an essential component of arabinogalactan biosynthesis, has been considered a novel target for developing new inhibitors against Tuberculosis. We aimed to discover DprE1 inhibitors utilizing the drug repurposing approach. Methods: A structure-based virtual screening of FDA and world-approved drugs database was carried out, and initially, 30 molecules were selected based on their binding affinity. These compounds were further analyzed by molecular docking with extra-precision mode, MMGBSA binding free energy estimation, and prediction of ADMET profile. Results: Based on the docking results and MMGBSA energy values- ZINC000006716957, ZINC000011677911, and ZINC000022448696 were identified to be the top three hit molecules with good binding interactions inside the active site of DprE1. These hit molecules were subjected to molecular dynamics (MD) simulation for a period of 100 ns to study the dynamic nature of the binding complex. MD results were in accordance with molecular docking and MMGBSA analysis showing protein-ligand contacts with key amino acid residues of DprE1. Conclusion: Based on their stability throughout the 100 ns simulation, ZINC000011677911 was the best in silico hit with an already known safety profile. This molecule could lead to future optimization and development of new DprE1 inhibitors. Graphical Abstract: ga1